THE STYLISTICS OG GRAPHIC NOVELS - Maripov Jalolkhan Kamoliddin o’gli; Mardiqulova Yulduz Abdujalil qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article describes the style and stylistic analysis of graphic novels as it bridges the worlds of literature and visual art. Graphic novels combine not only narrative storytelling but also vibrant colors and illustrations, which enhance readers' attention to novels in an unusual way. From the point of literature, graphic novels are a distinctive way of illustrating social and political issues through the combination of images and words within a text. In stylistics, how linguistic and visual elements such as panel layout, the use of color, and visual metaphors contribute to reflecting artistic effect in graphic novels. This article explores stylistic analysis of graphic novels, focusing on their visual style and language, and their connectivity in graphic novels.In addition to,this article can explain the structure and characteristics of graphic novel as an example of "Maus" by Art Spiegelman which  depicted the Holocaust through the lens of anthropomorphic animals,earning critical acclaim and widespread recognition.